Measurement of Practices-Knowledge-Attitudes of the Nursing Process: Systematic Review - Fabio Alberto Camargo-Figuera; María Alejandra Ortega-Barco; María Camila Rojas-Plata; Daniela Marín-Rodríguez; Lizeth Johana Alarcón-Meléndez; Beatriz Villamizar-Carvajal (Investigación y Educación en Enfermería, 2021)
Objective. To analyze the literature available on the psychometric properties of the instruments to measure knowledge, attitudes, and practices of the nursing care process.